Muslim Students' Role in the Development of Islamic Education for Generation Z - Erwin Kusumastuti; Ishna Shetia S; Astri Purwitasari; Chiara Yasmin Y.S; Ananda Churriyah R (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2024)
ENGLISH: Muslim Students' Role in the Development of Islamic Education for Generation ZObjective: This study aims to determine the urgency of the role of Muslim students in the development of Islamic education for Generation Z. Methods: This study used a quantitative research approach. The research subjects consisted of Muslim students actively involved in developing and delivering Islamic education to Generation Z. The data in this study were collected using a questionnaire developed based on the literature. The data in this study were collected using a questionnaire developed based on the literature. Data were analyzed using descriptive and inferential statistical approaches. Results: Muslim students can use technology to spread religious messages. The role of technology allows students to cooperate and share information about religion more widely and effectively. Conclusion: Muslim students play an important role in developing Islamic education for Generation Z, especially through digital technology, religious communities, and interactive learning methods. Contribution: This research references religious higher education institutions creating Islamic education work programs for Generation Z.INDONESIAN: Peran Pelajar Mahasiswa Muslim Dalam Mengembangkan Pendidikan Islam pada Generasi ZTujuan: Penelitian ini bertujuan untuk mengetahui urgensi peran mahasiswa muslim dalam pengembangan pendidikan agama generasi Z. Metode: Penelitian ini menggunakan pendekatan penelitian kuantitatif. Subjek penelitian terdiri dari mahasiswa Muslim yang aktif terlibat dalam mengembangkan dan menyampaikan pendidikan agama kepada generasi Z. Data dalam penelitian ini dikumpulkan menggunakan kuesioner yang dikembangkan berdasarkan literatur. Data dianalisis menggunakan pendekatan statistik deskriptif dan inferensial. Hasil: Mahasiswa Muslim dapat menggunakan teknologi untuk menyebarkan pesan-pesan keagamaan. Peran teknologi memungkinkan para pelajar untuk bekerja sama dan berbagi informasi tentang agama secara lebih luas dan efektif. Kesimpulan: Pelajar Muslim memainkan peran penting dalam mengembangkan pendidikan agama untuk Generasi Z, terutama melalui penggunaan teknologi digital, komunitas keagamaan, dan metode pembelajaran interaktif. Kontribusi: Penelitian ini berkontribusi sebagai referensi bagi lembaga pendidikan tinggi keagamaan dalam membuat program kerja edukasi agama untuk Generasi Z.